Analisis Deskriptif Performa Instalasi Pengolahan Air Limbah (IPAL) Berdasarkan Parameter BOD, COD dan TSS pada Industri Pengalengan Bekicot - Della Lusiana Fitri; Firra Rosariawari; Aprilia Permata Sari (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The Snail Canning Industry has the potential to impact the environment if wastewater with high organic compound content is not treated first. This study aims to analyze the performance of the Snail Canning Industry Wastewater Treatment Plant (WWTP) based on BOD, COD, and TSS parameters. The method used is descriptive, with primary data obtained through interviews and secondary data from laboratory test results. Measurements were taken at the inlet and outlet points of the WWTP, then compared with the quality standards based on the Regulation of the Minister of Environment No. 5 of 2014. The results showed that the WWTP succeeded in reducing the concentration of BOD from 201 mg/L to 6 mg/L, COD from 315 mg/L to 24 mg/L, and TSS from 25 mg/L to 6 mg/L. The reduction efficiency of each parameter was 97.01% for BOD, 92.38% for COD, and 76% for TSS. All outlet results met the established quality standards. This indicates that the wastewater treatment process at the IPAL functions effectively in reducing the levels of pollutant parameters in wastewater.